A Review on Cluster Based Data Aggregation Protocols in Wireless Sensor Network - Hiteshreddy, Obulapu; Singh, Pardeep; Chahuan, Siddharth (International Journal of Computer Sciences and Engineering, 2025)
Data aggregation process plays a key function in wireless sensor networks. The overall aim of data aggregation techniques is to assemble and combine information in an energy efficient way so that the lifetime of the network can be increased. In order to increase the energy efficiency and network lifetime, many researchers have proposed in data aggregation in wireless sensor networks since 1993.This research points to systematic study of subjects and challenges in data collection in wireless sensor networks. Data aggregation areas from six aspects: type of data aggregation techniques, secure data, privacy preserving data, cluster based data, energy efficient data and maximum lifetime of data aggregation. We accomplished a systematic literature review of data aggregation in wireless sensor networks in last two decades (1993-2015).we have identified 42 primary studies relevant to the aim of this research. After investigating this study, we found that six aggregation approach in wireless sensor networks. Data collection has various algorithms on the basis of performance criteria. Data collection techniques are promising in the area of wireless sensor networks. In this paper, we study cluster based data aggregation techniques approaches in networks and describe the various approaches in hierarchical networks protocols.